The kinetics of ammonium uptake and oxidation across the Southern Ocean - Mdutyana, Mhlangabezi; Sun, Xin; Burger, Jessica; Flynn, Raquel; Smith, Shantelle; Horsten, Natasha; Roychoudhury, Alakendra; Planquette, Hélène; Bucciarelli, Eva; Thomalla, Sandy; Ward, Bess; Fawcett, Sarah (Limnology and Oceanography, 2022)
International audience Central to the Southern Ocean's role in setting atmospheric CO2 is the seasonal alternation between upward mixing of nutrients and their subsequent consumption by phytoplankton. Active nutrient cycling within the mixed layer, including the release of ammonium (NH4+) and its removal by phytoplankton and nitrifiers, also affects Southern Ocean CO2 drawdown, yet remains poorly understood. We conducted kinetics experiments across the Southern Ocean south of Africa to investigate the dependence of NH4+ uptake (summer, winter) and oxidation (winter) on NH4+ concentration. NH4+ uptake followed a Michaelis–Menten function in both seasons, with the maximum rate (Vmax) decreasing poleward, apparently controlled mainly by light in winter and temperature in summer. The half-saturation constant (Km) increased poleward with increasing ambient NH4+ ([NH4+]amb) and was threefold higher in winter (150–405 nM) than in summer (41–115 nM), suggesting that summertime phytoplankton are adapted to low-NH4+ conditions while winter communities typically receive a higher NH4+ supply. NH4+ oxidation showed a high affinity for NH4+ (Km = 28–137 nM), suggesting a dominant role for ammonia-oxidizing archaea, and followed a Michaelis–Menten curve only when [NH4+]amb was ≤ 90 nM. Vmax was near-constant across the region regardless of [NH4+]amb, temperature, or light. From coincident mixed-layer NH4+ oxidation and iron measurements, we hypothesize that iron availability may (co-)limit the Vmax of NH4+ oxidation. If verified, this suggestion has implications for models that parameterize nitrification as a linear function of [NH4+]amb. Additionally, iron depletion may limit the role of mixed-layer nitrification, which is dominant in the winter Southern Ocean, in offsetting phytoplankton CO2 drawdown annually.